Sport as a tool for development and peace: tackling insecurity and violence in the urban settlement Cazucá, Soacha, Colombia. Issue 5 (19th October 2016) - Sobotová, Lenka; Šafaříková, Simona; González Martínez, María Alejandra
Abstract: The concept of 'Sport for Development and Peace' has gained new momentum. New challenges and questions have arisen, emphasising the need for more systematic ways to assess and measure the impact that sport and physical activities have had on addressing social exclusion, violence and poverty around the world. Therefore, this study aims to uncover the role of sport in the process of social inclusion and peacebuilding in the post-conflict context of Colombia. The country has recently experienced a historical moment as regards its future: the fourth peace process. From this perspective our research is set in the turbulent reality of the selected urban settlement of Soacha, a municipality spatially and economically connected to the country's capital, Bogotá. Within Soacha the settlement of Cazucá is mostly inhabited by internally displaced people and victims of the conflict, and is most associated with high rates of violence, crime and insecurity. Accordingly, the local NGO Tiempo de Juego develops its sport programmes in this area, to provide local youth and children with an alternative to the cycle of violence and exclusion. This article provides an insight into how these programmes contribute to changing the daily reality of their beneficiaries, and their perceptions of violence and security in the main places where sporting activities are held. It presents a small-scale pilot research study, using the tool of participatory mapping on a selected group of local youths who volunteer for the NGO to operate as peer leaders of different sport and art activities.